Holonic Business Process Modeling in Small to Medium Sized Enterprises - Mulyono, Nur Budi; Saputra, Tezar Yuliansyah; Rahmatsyah, Nur Arief (The Asian Journal of Technology Management (AJTM), 2009)
Holonic modeling analysis which is the application of system thinking in design, manage, and improvement, is used in a novel context for business process modeling. An approach and techniques of holon and holarchies is presented specifically for small and medium sized enterprise process modeling development. The fitness of the approach is compared with well known reductionist or task breakdown approach. The strength and weaknesses of the holonic modeling is discussed with illustrating case example in term of its suitability for an Indonesia’s small and medium sized industry. The novel ideas in this paper have great impact on the way analyst should perceive business process. Future research is applying the approach in supply chain context.Key words: Business process, holonic modeling, operations management, small to medium sized enterprise